Effect of 6-week core training programme on sagittal trunk flexion angle while running - Heng, Yu Jie (2019)
Recreational long distance runners typically run with an upright trunk posture. However, studies have shown that an upright trunk posture is commonly associated with an increased vertical ground reaction force (vGRF) and risk of patella-femoral syndrome (PFS). Therefore, recreational long distance runners are often exposed to the risk of PFS. While, core training is known to improve running trunk posture and core stability for long distance running, no study was conducted to identify if reduce sagittal trunk flexion angle and vGRF can be reduced from core training. Hence, the objective of this study is to investigate if a 6-week core training programme can decrease sagittal trunk flexion angle and vGRF while running, and hence, reduce the risk of PFS among recreational long distance runners. Twenty-eight recreational long distance runners between the ages of 19 – 30 participated in this study. Participants were randomly split into two-equal groups – control and experimental. The experimental group underwent a 6-week core training programme. Data on sagittal trunk flexion angle and vGRF were collected across three tests – pre-, mid-, and post-test. A mixed ANOVA test indicated no significant differences for interaction within-subjects factor x between-groups for both sagittal trunk flexion angle and vGRF. However, there is significant differences and large effect within the experimental group comparison for vGRF (p = 0.003 < 0.05; ⴄ2 = 0.206) – an average increase of 0.0522BW. Hence, core training is not a viable exercise protocol for reducing sagittal trunk flexion angle and vGRF. Instead, the sole development of core strength and stability could lead to increased risk of PFS.